2013
DOI: 10.1038/ajg.2013.94
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally Active Human Papillomavirus Is Strongly Associated With Barrett's Dysplasia and Esophageal Adenocarcinoma

Abstract: Transcriptionally active HR-HPV was strongly associated with BD and EAC, but was largely biologically irrelevant in BE and controls, suggesting a potential role in esophageal carcinogenesis. These data provide robust justification for further detailed longitudinal, interventional, and molecular studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 46 publications
4
71
0
Order By: Relevance
“…Among 77 patients with Barrett's esophagus, 17% had detectable HPV at the squamocolumnar junction whereas only 7% had detectable HPV within the columnar segment itself (P ¼ .06). 15 A similar finding was present among the 35 patients with dysplastic Barrett's esophagus, in whom 60% had detectable HPV at the squamocolumnar junction but fewer (40%) had detectable HPV within the more proximal parts of the columnar segment itself (P ¼ .04). Thus, studies sampling only columnar tissue may have very different results than those sampling other parts of the esophagus, although the significance of this with regard to the role of HPV in the pathogenesis of Barrett's esophagus is unknown.…”
Section: The Context Of Prior Researchsupporting
confidence: 72%
See 1 more Smart Citation
“…Among 77 patients with Barrett's esophagus, 17% had detectable HPV at the squamocolumnar junction whereas only 7% had detectable HPV within the columnar segment itself (P ¼ .06). 15 A similar finding was present among the 35 patients with dysplastic Barrett's esophagus, in whom 60% had detectable HPV at the squamocolumnar junction but fewer (40%) had detectable HPV within the more proximal parts of the columnar segment itself (P ¼ .04). Thus, studies sampling only columnar tissue may have very different results than those sampling other parts of the esophagus, although the significance of this with regard to the role of HPV in the pathogenesis of Barrett's esophagus is unknown.…”
Section: The Context Of Prior Researchsupporting
confidence: 72%
“…This study extended the same group's recently published work that showed that among 261 patients with Barrett's esophagus, 81 had detectable HPV DNA. 15 The investigators are appropriately cautious in recommending further studies to evaluate whether either HPV or p53, independently or jointly, might serve as risk markers for more refractory/aggressive disease in clinical trials.…”
Section: The Context Of Prior Researchmentioning
confidence: 99%
“…HPV infection is believed to be responsible for the dramatic rise in head and neck cancers in western countries, which leads to a suspicion that HPV may also play a role in EAC. However, very few investigations of an association between HPV and EAC have been reported, and no evidence of association was found according to these reports [42] . Recently, Rajendra and colleagues [42,43] reported for the first time that transcriptionally active hrHPV was strongly associated with EAC.…”
Section: Hpv and Eacmentioning
confidence: 94%
“…However, very few investigations of an association between HPV and EAC have been reported, and no evidence of association was found according to these reports [42] . Recently, Rajendra and colleagues [42,43] reported for the first time that transcriptionally active hrHPV was strongly associated with EAC. They also showed that increasing viral load and active virus transcription were significantly associated with disease severity in the Barrett's metaplasiadysplasia-adenocarcinoma pathway.…”
Section: Hpv and Eacmentioning
confidence: 94%
“…A prospective study determined the prevalence of biologically active HPV in esophageal epithelium of patients in BE patients with and without dysplasia and EAC. HPV DNA was estimated by nested PCR and viral transcriptional activity by E6/7 oncogene mRNA expression and p16INK4A immunohistochemistry in fresh frozen and paraffin-embedded esophageal biopsies in patients with BE, BE-related dysplasia, EAC, and controls [53]. Compared to controls, HPV positivity was more common in BE-related dysplasia (68.6 % vs. 18 %, incidence rate ratio 2.94, 95 % CI 1.78 -4.85, pG0.001) and EAC (66.7 % vs. 18 %, incidence rate ratio 2.87, 95 %CI 1.69 -4.86, pG0.001), but not more common in BE patients.…”
Section: Human Papilloma Virusmentioning
confidence: 99%